2016
DOI: 10.1016/j.jand.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake Patterns Are Consistent Across Seasons in a Cohort of Healthy Adults in a Metropolitan Population

Abstract: Background Current literature provides conflicting data regarding seasonal variability in dietary intake. Objective To examine seasonal variation in dietary intake in healthy adults from the metropolitan Washington, DC area. Design This study utilized an observational cohort design. Participants/setting Male and female healthy volunteers (n=103) between the ages of 18–75 years were recruited from the metropolitan Washington, DC area to participate in a clinical study at the National Institutes of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
4
18
2
Order By: Relevance
“…Seasonality of total energy and macronutrient intake varied between countries and even between sexes. These results are in agreement with the literature, where discordant findings regarding seasonality of total energy intake and fat have been reported [1,2,4,8,9,23,24]. A study conducted in China showed no seasonality for the main nutrients and only for a selected number of micronutrients such as retinol, ascorbic acid, potassium and calcium [24].…”
Section: Seasonality Analysessupporting
confidence: 91%
See 2 more Smart Citations
“…Seasonality of total energy and macronutrient intake varied between countries and even between sexes. These results are in agreement with the literature, where discordant findings regarding seasonality of total energy intake and fat have been reported [1,2,4,8,9,23,24]. A study conducted in China showed no seasonality for the main nutrients and only for a selected number of micronutrients such as retinol, ascorbic acid, potassium and calcium [24].…”
Section: Seasonality Analysessupporting
confidence: 91%
“…However, the findings will probably not apply to more developing countries, where dietary intake depends on available crops. Our results thus support the conclusion of a previous US study [8] and suggest that adjusting for season might no longer be necessary when assessing dietary intake in specific settings.…”
Section: Trends In Seasonalitysupporting
confidence: 89%
See 1 more Smart Citation
“…Most fruits ripen in summer and the actual availability and accessibility of fruit in summer might be much higher than that of other seasons. Other studies have also found increases in vegetable and fruit consumption in summer compared to winter [16,17,33,34,35]. …”
Section: Discussionmentioning
confidence: 92%
“…For example, Bernstein et al (2016) found that intake of energy, macronutrients, and food groups by healthy adults in metropolitan Washington D.C. did not vary between seasons. Yet, seasonal differences in protein (Mori et al, 1981), lipid (Mori et al, 1981;Owaki et al, 1996), and dietary fiber (Owaki et al, 1996;Tokudome et al, 2002) intake were observed in Japanese studies.…”
Section: Discussionmentioning
confidence: 99%